Peningkatan Profesionalisme Tenaga Kesehatan melalui Manajemen Kepemimpinan yang Efektif - Diva Taswin; Anindya Sabrina A; Sayla Ramadani; Selviani; Sriwahyuni Siregar; Widya Aliska Hariana; Ibnaty Salsabila; Tiur Dini Hariani Simbolon; Lila Mashannum Harahap; Dhea Puspita (Yayasan Salam Cerdas Al-Fattah, 2025)
The professionalism of healthcare workers serves as the primary foundation for improving the quality of health services across various healthcare facilities. One of the key factors that significantly contributes to building such professionalism is effective leadership management. Good leadership can create a conducive work environment, encourage interprofessional collaboration, and foster commitment to ethics and professional responsibility. This study aims to analyze the relationship between leadership effectiveness and the enhancement of healthcare workers’ professionalism in hospitals and health service centers. The research employed a descriptive qualitative approach by collecting data through literature studies and interviews with several healthcare workers in regional hospitals. The findings indicate that participatory and transformational leadership styles can improve work motivation, professional responsibility, and the quality of patient care. Therefore, the implementation of effective leadership management becomes a strategic key in developing highly professional and integrity-driven healthcare personnel.